Housing prices and submarkets in Mexico City: A hedonic assessment - Sobrino, Jaime (Estudios Económicos de El Colegio de México, 2014)
The objective of this paper is to explore the role of some quantitative variables in explaining housing prices, and how these variables can be used for the spatial delimitation of housing submarkets. The methodological strategy incorporates issues from the spatial economic theory, and an econometric model of hedonic prices to analyze the main characteristics of housing demand in Mexico City. Housing submarkets are delimited by using a statistical multivariate tool, two-step, log likelihood cluster analysis, in terms of intra-urban relative house differentials. The models are estimated using cross-sectional data from the 2010 micro-data of Mexico’s National Survey of the Households’ Incomes and Expenditures.